2013
DOI: 10.1093/molehr/gat033
|View full text |Cite
|
Sign up to set email alerts
|

Functional human sperm capacitation requires both bicarbonate-dependent PKA activation and down-regulation of Ser/Thr phosphatases by Src family kinases

Abstract: In all mammalian species studied so far, sperm capacitation correlates with an increase in protein tyrosine (Tyr) phosphorylation mediated by a bicarbonate-dependent cAMP/protein kinase A (PKA) pathway. Recent studies in mice revealed, however, that a Src family kinase (SFK)-induced inactivation of serine/threonine (Ser/Thr) phosphatases is also involved in the signaling pathways leading to Tyr phosphorylation. In view of these observations and with the aim of getting a better understanding of the signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 54 publications
8
102
1
Order By: Relevance
“…Even for sperm, the dosage of a certain inhibitor is deferent between the species. The IC 50 of the SFK (Src family kinase) inhibitor SK1606 in human sperm was five times lower than the CCK receptors regulate protein phosphorylation one observed in mouse sperm (Krapf et al 2010, Battistone et al 2013). Our present results showed that 5 mM CCK1 or CCK2 receptor antagonist could stimulate the increase of tyrosine phosphorylation ( Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Even for sperm, the dosage of a certain inhibitor is deferent between the species. The IC 50 of the SFK (Src family kinase) inhibitor SK1606 in human sperm was five times lower than the CCK receptors regulate protein phosphorylation one observed in mouse sperm (Krapf et al 2010, Battistone et al 2013). Our present results showed that 5 mM CCK1 or CCK2 receptor antagonist could stimulate the increase of tyrosine phosphorylation ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…The serine/threonine phosphorylation of PKA substrate proteins is a critical event on the upstream of sperm capacitation-associated protein tyrosine phosphorylation (Battistone et al 2013). To examine whether CCK receptor antagonists have the influence on PKA substrate phosphorylation, we determined the change of PKA substrate phosphorylation in sperm treated with CCK receptor antagonists.…”
Section: Cck Receptor Antagonists Can Accelerate Pka Substrate Phosphmentioning
confidence: 99%
“…This plot was then used to determine the sperm intracellular cAMP concentration by interpolation. This assay was used recently for human sperm (39). Alternatively, cAMP levels were measured using the direct cyclic AMP ELISA kit (Enzo Life Sciences/Biomol, Farmingdale, NY).…”
Section: Methodsmentioning
confidence: 99%
“…5). In addition to calcium, BSA and bicarbonate in the capacitating medium are wellknown to affect membrane fluidity either directly or indirectly through activation of sperm adenylyl cyclase and increase in intracellular cAMP concentration in species such as mouse and human (Wang et al 2007;Battistone et al 2013). Phorbol esters have been reported as capable of initiating acrosomal exocytosis in capacitated human sperm (De Jonge et al, 1991;Rotem et al, 1992) and in zona-induced mouse sperm (Lee et al, 1987); as well as of producing early events leading to acrosomal exocytosis in bull (Lax et al, 1997).…”
Section: Discussionmentioning
confidence: 99%